2021
DOI: 10.1093/abm/kaab030
|View full text |Cite
|
Sign up to set email alerts
|

Change in Dysfunctional Sleep-Related Beliefs is Associated with Changes in Sleep and Other Health Outcomes Among Older Veterans With Insomnia: Findings From a Randomized Controlled Trial

Abstract: Background Cognitive behavioral therapy for insomnia (CBTI) targets changing dysfunctional sleep-related beliefs. The impact of these changes on daytime functioning in older adults is unknown. Purpose We examined whether changes in sleep-related beliefs from pre- to post-CBTI predicted changes in sleep and other outcomes in older adults. Method Data included … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 57 publications
2
11
0
Order By: Relevance
“…A recent study has suggested that pain-affected older adults' belief that they need to sleep more the next day or night to make up for lost sleep attributed to their pain. 69 We found similar findings with 61.3% of participants reporting that pain disturbed their sleep and half of the participants had a strong belief that without proper sleep on a given night, they would need to catch up the next day by napping or the next night by sleeping longer. Furthermore, our findings suggest that patients with spine pain have dysfunctional beliefs related to expectations for sleep and consequences of insomnia that may be related to sleeprelated impairment associated with their pain.…”
Section: Dysfunctional Beliefs Predict Pain Interferencesupporting
confidence: 82%
See 2 more Smart Citations
“…A recent study has suggested that pain-affected older adults' belief that they need to sleep more the next day or night to make up for lost sleep attributed to their pain. 69 We found similar findings with 61.3% of participants reporting that pain disturbed their sleep and half of the participants had a strong belief that without proper sleep on a given night, they would need to catch up the next day by napping or the next night by sleeping longer. Furthermore, our findings suggest that patients with spine pain have dysfunctional beliefs related to expectations for sleep and consequences of insomnia that may be related to sleeprelated impairment associated with their pain.…”
Section: Dysfunctional Beliefs Predict Pain Interferencesupporting
confidence: 82%
“…Understanding the unique and specific contributions of both health literacy and maladaptive behavior is important to recognize to effectively target treatment interventions (ie, more focus on education or behavior change). Changing sleep-related beliefs has been associated with improvements in sleep and other health outcomes in older adults and veterans 69. Understanding how changes in dysfunctional attitudes and beliefs are correlated with changes in pain-related outcomes longitudinally would also help improve our understanding of meaningful targets for intervention.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, we chose the medium Cohen's d effect size of 0.50 for the sample size calculation, mostly due to the differences in the number of given CBT-I sessions across studies. Treatment in this RCT includes 4 sessions, while other reviewed studies include 5 (37,38,41) and 8(39, 40) sessions, respectively. It is reasonable to assume that treatment effectiveness may decrease with fewer number of sessions.…”
Section: Sample Sizementioning
confidence: 99%
“…Since chronic stress can lead to depression, stress induced by constant worry about sleep may play a role in the development of depression [70e73]. CBT-I also improves dysfunctional thoughts and attitudes about sleep [73]. Therefore, improved mental health after CBT-I may be attributable to reduced worry about sleep rather than improved sleep itself.…”
Section: Overall Random Effects Modelmentioning
confidence: 99%